Examining Internal and External Physical Workloads Between Training and Competitive Matches Within Collegiate Division I Men's Soccer. Issue 12 (29th December 2021) - Anderson, Travis; Adams, William M.; Martin, Kerry J.; Wideman, Laurie
Abstract: Anderson, T, Adams, WM, Martin, KJ, and Wideman, L. Examining internal and external physical workloads between training and competitive matches within collegiate Division I men's soccer. J Strength Cond Res 35(12): 3440–3447, 2021—A direct analysis comparing differences in the demands of competition relative to in-season training in Division I collegiate soccer players has yet to be reported. Thus, the primary purpose of this study was to compare the absolute and relative internal and external workloads measured during training with competitive matches. Twenty-six male college soccer players were monitored over 2 consecutive seasons using a GPS and heart rate (HR) telemetry system. Differences between outdoor training sessions and competitive matches were analyzed for internal and external absolute and relative training workloads. Differences in training workloads between the 3 days before a match were also analyzed. Absolute time in HR zone 4 (80–89% of HRmax) and 5 (90–100% of HRmax); accelerations in zone 1 (0.50–0.99 m·s −2 ), zone 2 (1.00–1.99 m·s −2 ), and zone 3 (2.00–2.99 m·s −2 ); all negative acceleration zones; training load; and estimated energy expenditure were greater in competition than training ( p < 0.05). By contrast, when comparing training and competition values using metrics relative to session duration, relative workload in trainings were greater than competition for HR zone 1 (50–59% of HRmax), zone 2 (60–69% of HRmax), zone 3 (70–79% of HRmax), and zone 4 (80–89% of HRmax) and all acceleration and negative acceleration zones. In addition, absolute training workloads were generally greatest 3 days prior ( p < 0.01), but not different 2 days before the competitive match. Absolute physical workloads of competition are significantly greater than those achieved during training; however, these differences and impact on the physical condition of players are mitigated by the greater relative workloads achieved during training. These results provide meaningful metrics that may lead to insights into proper conditioning and in-season workload management for Division I collegiate soccer programs.